Mechanically powered negative pressure dressing reduces surgical site infection after stoma reversal - Brian Williams, MD; Aubrey Swinford, MD; Jordan Martucci, MD; Johnny Wang, MD; Jordan R. Wlodarczyk, MD; Abhinav Gupta, MD; Kyle G. Cologne, MD; Sarah E. Koller, MD; Christine Hsieh, MD; Marjun P. Duldulao, MD; Joongho Shin, MD (Surgery Open Science)
Background: The use of closed-incision negative pressure wound therapy (ci-NPWT) has been shown to reduce postoperative wound complications and surgical site infections (SSI) after stoma closures. However, use of this approach has not been widely adopted due to high cost of the devices. We present a novel approach to stoma closure in which a self-contained mechanically powered negative pressure dressing (MP-NPD) is applied to primarily closed stoma reversal wounds. We hypothesized that SSI and wound complication rates would be improved compared to traditional stoma closure methods. Methods: This was a prospective investigator-initiated study, in which consecutive patients that underwent stoma reversal with primary stoma wound closure dressed with MP-NPD from May 2021–March 2022. 30-day outcomes from the study group, including surgical site infection, other wound complications, hospital length of stay (LOS), and readmission rates, were then reported. Results: Forty-six patients undergoing local ileostomy or colostomy closure were identified for the study group. Patient demographics and surgical variables were reported. One (2.2 %) patient in the study cohort developed superficial SSI within 30 days of their surgery. Post-op LOS in the study group versus was 4.1 days. Conclusion: Intestinal stoma reversal wounds closed primarily and dressed with the MP-NPD dressings had very low stoma site SSI rates. These results are promising as they pertain to the use of MP-NPD in stoma reversal procedures, however further large prospective RCTs with a matched control group could help better corroborate these findings.